Making an effort for free – volunteers' roles in destination-based storytelling. Issue 7 (6th June 2016) - Olsson, Anna Karin; Therkelsen, Anette; Mossberg, Lena
Abstract : Many destinations are dependent on volunteers. Storytelling is one of the areas to which volunteers are increasingly contributing; however, the role of volunteers has been offered only sporadic attention. The aim of this study is to provide insights into volunteer involvement by studying volunteers as destination stakeholders with focus on their roles, influence, and contribution. A cross-case analysis of three Nordic cases is undertaken. A theoretical framework is developed based on volunteer tourism, stakeholder theory, and marketing literature on storytelling. A three-phase model of the storytelling process is developed. Findings show substantial variation. Unsurprisingly, early inclusion of volunteers result in substantial influence on the storytelling concept, however, this does not guarantee volunteer involvement later on. Conversely, late inclusion of volunteers does not necessarily hinder engagement among volunteers in the execution of the stories. All cases demonstrate that developing a strong concept that can tie together the efforts of stakeholders across professional and volunteer divides is a major challenge. The results point at the importance of strategic goals coordinating storytelling activities, volunteer inclusion, and 'use' of volunteers' local knowledge and enthusiasm in all phases of the destination-based storytelling process planned along with strategic goals such as 'selling place' or 'building community'.